Scientific and technological innovation cooperation network of the Greater Bay Area in South China: A social network analysis - Chuyi Shen; Zhenjie Yang; Fat-iam Lam; Sio wa Tam; Wenping Yang; Yunxin Li (PLoS ONE, 2025)
Regional innovation cooperation focused upon either regions within one nation or transnational regions. Different from the discussion in the existing literature, the Guangdong- Hong Kong-Macao Greater Bay Area exists as an exceptional cross-border city-to-city cooperation under “one country, two systems”. Based on the social network analysis on co- patents in the Greater Bay Area, this paper aims to investigate the models and features of the innovation cooperation network of science and technology in the Greater Bay Area and the different characteristics of collaboration policy on cross-border knowledge flow before and after 2015. The results show that the innovation network of science and technology in the Greater Bay Area has a loosely structured pattern, with Hong Kong-Shenzhen-Guangzhou as a prominent hub. This structure portrays multiple centers that radiate out to its peripheries. The national policy launched in 2015 reduces the cooperation barriers and promotes the cross-border collaboration. The universities and research institutes possess significant intermediary roles and innovation autonomy in the scientific and technological innovation cooperation network of the Greater Bay Area.